Tranexamic acid did not attenuate the acute rise in plasma syndecan-1 in a severely injured cohort: a laboratory analysis of the PATCH clinical trial - Elissa M. Milford; Dusan Marjanovic; Heidi Ho; Steven Wallis; Dominik F. Draxler; Biswadev Mitra; Russell L. Gruen; Robert Medcalf; Stephen Bernard; Colin McArthur; Marc Meagele; Brian Burns; et al. (Intensive Care Medicine Experimental)
Abstract Background Injury to the vascular endothelium occurs in up to 34% of patients acutely following severe traumatic injury and can be quantified clinically by measuring the plasma concentration of syndecan-1 (SDC-1). Tranexamic acid (TXA) attenuates endothelial damage in animal and cell culture models and has been associated with lower SDC-1 levels after prehospital TXA administration. The aim of this study was to assess the association of prehospital TXA on SDC-1 levels in a more severely injured prehospital cohort. Methods The PATCH-Trauma trial randomised patients to receive pre-hospital TXA or placebo. In this sub-cohort, SDC-1 was measured in blood samples collected on hospital admission, at 8 and 24 h. Relationships between SDC-1 levels over time, treatment groups, and outcomes were analyzed using regression modelling controlling for potential confounding factors. Results There were 89 patients included, with 57 administered TXA and 32 administered placebo (per protocol). SDC-1 levels were available in 87 patients on arrival to hospital, 70 at 8 h, and 69 at 24 h. Patients had a median SDC-1 on admission of 106 ng/mL (IQR 88–137). There was no effect of TXA treatment on SDC-1 levels over the first 24 h of hospital admission, even after controlling for known confounders. There was no association between SDC-1 level at any time point and the development of deep vein thrombosis or sepsis, mortality at 28-days, or days alive and out of hospital, even after adjustment for confounding factors. Conclusion Administration of TXA, initiated pre-hospital, did not affect SDC-1 levels in the first 24 h of hospital admission in this severely injured cohort. Further research is required to elucidate the mechanisms of the effect of TXA on the endothelium as well as the utility of SDC-1 as an endothelial biomarker.